Oral Contraceptive Types in Relation to ABO Blood Groups Among Saudi Women of Different Reproductive Age Groups and Impact on Venous Thromboembolism - Mohamed, Abdulrahman B. O. (Clin Appl Thromb Hemost, 2020)
Saudi women have recently started using oral contraceptives (OCs), which has led to risk of venous thromboembolism (VTE). The risk varies with the type of OC generations used, and with OC use the risk for VTE increases by 2- to 6-fold. This study evaluated the effect of OC types in relation to ABO blood group on the risk of VTE among Saudi women. Thrombin generation (TG) was measured in the plasma of the women in the presence and absence of platelet rich plasma, platelet poor plasma and thrombomodulin or activated protein C. OC usage increased TG parameters ETP and Peak height by 9.81% and 16.04%, respectively. An increased risk of VTE was seen among women on third generation OCs as compared to those on second generation products. Within OC generations, we found that for women using fourth generation OCs, their ETP increased by 36.18% as compared to those using second generation and by 6.07% in those using third generation compared to those using second generation. There was significant difference with respect to ABO blood groups and OC generation types, but larger sample size is required. Women who are 40 years and older and using third generation OC had a higher risk of having thrombosis (11.84%), as compared to those using second generation OC (8.79%) and to those using fourth generation OC (5.03%). An association between different OC groups and non-O blood group in thrombosis generation was noted. TG parameters were significantly increased in relation to BMI when comparing to OC users versus non-users. In addition, inhibition of TG parameters in the presence of recombinant human thrombomodulin (TM) and activated protein C (APC) were significantly increased.